Relationship Between Mangrove Condition and Socio-economic Livelihoods of Fishermen Traps in Central Tapanuli - Muna, Zakyatul; Fuah, Ricky Winrison; Khobir, Muhammad Latiful; Andhini, Nadia; Fazri, Kurniawan; Dariansyah, Moch Ricky; Marbun, Ahmad Sadiqi; Purba, Bima Theo Cristian (International Journal of Marine Engineering Innovation and Research, 2024)
Central Tapanuli Regency is a region that has significant potential in the fisheries sector, mainly traditional fisheries, due to its extensive mangrove ecosystem and lengthy coastline. Mangroves are essential for the livelihood of local fishing, as they protect the marine environment and serve as a barrier against coastal erosion. The mangrove ecosystem in Central Tapanuli Regency is experiencing increased pressure due to land conversion, illicit logging, and other human activities, as research surveys indicate. This pressure has a negative impact on the productivity of catches and the welfare of fishermen. This risk is undoubtedly a significant concern; the ecological value of the mangrove ecosystem may be diminished, resulting in a decrease in the catch of local trap fishermen. Consequently, this research is necessary for the local government to reference when developing mangrove management strategies. This investigation aimed to assess the state of the mangrove ecosystem in Tapian Nauli Bay and the correlation between mangrove conditions and the socio-economic status of crab trawl fishermen. The investigation was conducted in Central Tapanuli, specifically in Tapian Nauli Bay. Surveys and interviews with respondents were implemented to accumulate data. Descriptive and correlational analyses are implemented. The results of this study indicated that 60% of the mangroves in Tapian Nauli Bay were in excellent condition, while only 30-40% were in poor condition. The income of bubu fishermen is significantly influenced by the presence of mangroves, as the catches they capture increase, thereby improving their livelihoods.